Cerebral haemodynamic effects of changes in positive end expiratory pressure in preterm infants. Issue 4 (April 1989) - Shortland, D B; Field, D; Archer, L N; Gibson, N A; Woods, K L; Evans, D H; Levene, M I
Abstract : The effects of changes in positive end expiratory pressure (PEEP) on cerebral blood flow velocity, arterial blood gases, and mean arterial pressure were studied in newborn infants. In mechanically ventilated premature infants with severe respiratory disease, an increase in PEEP from 2 to 6 cm H2O was associated with an increase in cerebral blood flow velocity. There was no significant change in mean arterial blood pressure. There was a significant increase in PaO2 and PaCO2 for every stepwise rise in PEEP. Multivariate regression analysis showed that 72% of the effect on cerebral blood flow velocity was attributable to PaCO2 alone and that any change in blood pressure was not likely to contribute to these changes. There was no evidence that changes in PEEP within the commonly used range adversely affected the neonatal cardiovascular or cerebral circulations.